(untitled) (Fiep Bulletin - online, 2013)
Pain is a subjective manifestation, may be a sign of the body that something is wrong. Different instruments have been used to evaluate it, and sensitive and reliable measures are needed for proper diagnosis and treatment. One of the tools used is dolorimeter pressure. The objective of this study was to evaluate the inter-rater reliability for determining the threshold of pain by pressure algometer. The sample group consisted of 20 healthy volunteers, young adults of both genders, students of the institution, the University state of Paraná (UNIOESTE), campus Cascavel. For the evaluation of pressure sore was used pressure algometer (Kratos ®), and an apparatus capable of producing up to 50 Kgf, being administered by different raters for three consecutive days. Regarding the results, compared inter-rater significant difference in all evaluations, but the correlations ranged from low to high power. It is concluded that the evaluation of the pain threshold algometer pressure is most reliable when applied by a single evaluator.